Effect of age and endometrial degenerative changes on uterine blood flow during early gestation in mares - Ferreira, João Carlos Pinheiro [UNESP]; Canesin, Heloísa de Siqueira [UNESP]; Ignácio, Fernanda Saules [UNESP]; Rocha, Noeme Sousa [UNESP]; Pinto, Carlos Roberto; Meira, Cezinande de [UNESP] (Elsevier B. V., 2015)
The present experiment was divided into three studies to investigate the effect of age and endometrial degeneration on uterine blood flow of mares. In study 1, the influence of semen infusion and conception was evaluated using noninseminated (non-AI), inseminated nonpregnant (AI-NP), and inseminated pregnant (AI-P) mares (n = 7 mares/group). In study 2, the effect of age was investigated using young (≤6 years), adult (from 8 to 12 years), and old (≥15 years) pregnant mares (n = 7 mares/group). In study 3, uterine blood flow was also characterized in pregnant mares (n = 7 mares/group) with minimal, moderate, or severe endometrial degenerative changes (GI, GII, and GIII, respectively). Uterine vascular perfusion and pulsatility index from mesometrium attachment arteries were recorded daily from Day 0 (day of ovulation) to Day 12 and between Days 0 and 20 in nonpregnant and pregnant mares. Analysis according to the position of the embryo (uterine horn with embryo vs. opposite horn) was performed from Day 12 until Day 20. In study 1, increased uterine vascular perfusion and decreased pulsatility index were detected (P < 0.001) between Days 3 and 5 in non-AI and AI-P mares, whereas the uterine vascular perfusion of AI-NP mares did not change (P > 0.05) throughout the experiment. In study 2, the vascular perfusion of the uterine horn with embryo was higher (P < 0.001) than in the opposite uterine horn from Day 12 until Day 20 in both young and adult mares. With exception of Day 15, both uterine horns of old mares showed similar (P > 0.1) vascular perfusion from Day 12. In study 3, vascular perfusion of both uterine horns was lower (P < 0.001) in GIII mares than in GI and GII mares. After Day 15, the scores for uterine vascular perfusion were consistently greater (P < 0.001) in the uterine horn with embryo than in the opposite horn in GI mares. Results showed, for the first time, the reduced blood flow of the gravid uterus during early gestation in older mares and in mares with significant endometrial degeneration.
Keywords: Doppler; Embryo; Hemodynamics; Pregnancy; Uterus